Analisis Strategi Perdagangan Internasional Pada High Income Countries - Arista Yusuf Pradana; Hasmarini, Maulidyah Indira (Lembaga Teewan Journal Solutions, 2026)
International trade is a crucial component of a nation’s economy because increasing trade activity can expand state revenue and stimulate economic growth. Therefore, economic openness becomes an important concern for governments worldwide. This study analyzes the effects of inflation, military government expenditure, industrial sector dynamics, and investment policies on international trade performance in High-Income Countries during the pandemic era from 2018–2023 using panel data analysis. The Fixed Effects model results indicate that inflation and industrial value added positively influence trade openness. In contrast, military expenditure and FDI outflow negatively affect trade openness. Meanwhile, the percentage of labor force employed in the industrial sector and FDI outflow do not show a significant effect on trade openness. The findings suggest that governments should maintain inflation stability to ensure stable prices of essential commodities, especially during crises such as the pandemic period. In addition, governments are encouraged to strengthen the industrial sector both domestically and internationally, as higher industrial value added has been proven to significantly improve trade openness and international trade performance in high-income countries during the pandemic era and support sustainable economic growth.